(3eSGFd GdeObb aj GdcaQ GdHQF Yf GdGjeGfs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3hGdMeO ddg hbafG Ydi eSGFd GdTjN Gdedcjf SdjeGf Hf eMeO Hf YdjGf , Sdeg Gddg hMGWg , GdJi LQJ Hjfg hHjf GdeWQai GdPi PcQ Gfg ef CObge ESJNQGLkG s
(3BNQgG (B:s
(3hbO ChOYfG TQM GdQSGdI GdfGVLI aJage Pdc ehabkG Ef TGA Gddg JYGdi Je Hef Gddg hdWag s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3cJHJ GdYfGhjjf HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
Keywords: (3Gdabg GdESdGejs